Perempuan: Hutan dan Salingka Danau Singkarak (Kajian Etnografi Feminis Terhadap Pemanfaatan Sumber Daya Alam) - sri setiawati; Hairul Anwar; Rizqa Gumilang (Universitas Andalas, 2023)
This paper describes the use of natural resources, especially forests and lakes, by Minang women in Nagari Guguak Malalo, Batipuah Selatan District, Tanah Datar District, West Sumatra Province. The Minangkabau people who adhere to the matrilineal system are seen as entities and identities of indigenous peoples born from the historical process of the development of Minangkabau indigenous peoples. Minang women, part of the indigenous community, also utilize natural resources in the Mutual Lake. Experience with women's groups in forestry is much more limited (compared to men). The problem in this study is how the use of forests and lakes by Minang women in the Nagari Guguak Malalo. So the purpose of this study is to describe the uses that Guguak Malalo women made of lakes and forests. Gender-based Applied Anthropology Research relies on a qualitative approach that is descriptive and holistic. Through case studies on Minang women in Nagari Guguak Malalo who utilize the forests and lakes of Singkarak. Collecting data through literature study techniques, in-depth interviews, participatory observation and FGD. The data that was successfully collected was then analyzed descriptively qualitatively. The findings of this study are that women in Nagari Guguak Malalo have an important role in the utilization of natural resources, especially the use of lakes and forests. Utilization orientation is not only for subsistence needs, but also for market orientation. Increasing the use of natural resources for women really needs the attention of all parties.